Bike Battles : A History of Sharing the American Road - Longhurst, James (Book collections on Project MUSE., 2015)
Americans have been riding bikes for more than a century now. So why are most American cities still so ill-prepared to handle cyclists? James Longhurst, a historian and avid cyclist, tackles that question by tracing the contentious debates between American bike riders, motorists, and pedestrians over the shared road.